Identification of Ras farnesyltransferase inhibitors by microbial screening. - Hara, M (1993)
A microbial screen using a yeast strain with conditional deficiency in the GPA1 gene was carried out to search for inhibitors of protein farnesyltransferase (PFT). A strain of Streptomyces was found to produce active compounds named UCF1-A, UCF1-B, and UCF1-C. Structural determination of these compounds revealed that UCF1-C is identical to the known antibiotic, manumycin, whereas UCF1-A and UCF1-B are structurally related to manumycin. All three UCF1 compounds suppress the lethality of gpa1 disruption, with UCF1-C exhibiting the strongest activity. UCF1 inhibits yeast as well as rat brain PFT. Fifty percent inhibition of yeast PFT activity is observed with 5 microM UCF1-C. Kinetic analyses of the inhibition suggest that UCF1-C acts as a competitive inhibitor of PFT with respect to farnesyl pyrophosphate, exhibiting a Ki of 1.2 microM, whereas the same compound appears to act as a noncompetitive inhibitor of PFT with respect to the farnesyl acceptor, the Ras protein. UCF1-C shows significant activity to inhibit the growth of Ki-ras-transformed fibrosarcoma, raising the possibility of its use as an antitumor drug.